2022
DOI: 10.1039/d2ja00082b
|View full text |Cite
|
Sign up to set email alerts
|

Ce and Nd stable isotope purification and determination of geological samples by MC-ICP-MS

Abstract: Combined study of Ce and Nd stable isotopic is a promising way because Ce and Nd behave similarly in geological processes and distinctively in the redox reaction. However, sequential purification...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 67 publications
(159 reference statements)
0
14
0
Order By: Relevance
“…Ce, Nd, Sm, and Eu isotope fractionations analyzed in this study compared to literature values relative to OL-REE. Ce: refs ; Nd: refs , , , and ; Sm: ref ; Eu: refs and .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ce, Nd, Sm, and Eu isotope fractionations analyzed in this study compared to literature values relative to OL-REE. Ce: refs ; Nd: refs , , , and ; Sm: ref ; Eu: refs and .…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear field shift also causes the subdued isotope fractionation of 142/140 Ce compared to 136/140 Ce and 138/140 Ce at low temperature since more eminent effects of NFS partially canceled equilibrium MDF on 142/140 Ce . As mentioned in Section , the isotopic fractionation reported using 136 Ce and 138 Ce DS is calculated from 142/140 Ce (also see ref ), while all the isotope analyses using SSB also only reported 142/140 Ce due to the extremely low natural abundances of 136 Ce and 138 Ce. , In the discussion below, we consider only Ce isotope fractionation reported as 142 Ce/ 140 Ce. As the NFS scales with 1/ T and equilibrium MDF scales with 1/ T 2 , the maximum equilibrium isotope fractionation of 142/140 Ce is achieved at medium temperature (∼550 K; Figure 3 in ref ).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a C-SSBIN model was successfully applied to Ce and Nd stable isotope measurements using Sm and Eu internal normalization, respectively. 33,37,38,[49][50][51] This model used an established isotope ratio to calibrate the target element isotope ratios based on mass-dependent fractionation laws. The short-term dri of mass bias between analytes and standards was well managed and not affected by matrix effects.…”
Section: C-ssbin Methods For High Intermediate Precision Sm Isotope A...mentioning
confidence: 99%
“…Therefore, the resin is highly efficient for Nd-Sm separation, which has been conrmed in previous studies on the stable isotope analysis of Nd. [37][38][39][40][41][42] In addition, Sm has much a weaker affinity on TODGA resin in 1.5 M to 0.8 M HCl media compared to Eu and Gd. This difference suggests that TODGA resin has further potential to separate Sm from Nd, Eu, and Gd if a proper elution protocol is developed.…”
Section: Evaluation Of the New Sm Separation Protocolmentioning
confidence: 99%
“…39 During eluting REEs, LN resins are typically loaded in dilute acid and stripped with more concentrated acid, 17 while DGA resins are loaded in more concentrated acid and stripped with dilute HCl. [40][41][42] The AG 50W-X8 resin is a strong cation exchanger with sulfonic acid functional groups attached to a styrene divinylbenzene copolymer lattice. Li et al 43 reported REEs behavior using AG50W-X8 with a-HIBA and observed that the distribution coefficients (K d ) of heavy REEs are lower than light REEs, contrary to that of DGA resin.…”
Section: Nd Isotopic Fractionation During Column Chromatographymentioning
confidence: 99%